2002
DOI: 10.1148/radiol.2221001743
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Claudication: Cost-effectiveness of Revascularization versus Exercise Therapy

Abstract: The results suggest that, on average, the expected gain in effectiveness achieved with bypass surgery for intermittent claudication is small compared with the costs. Angioplasty performed whenever feasible was more effective than was exercise alone, and the cost-effectiveness ratio was within the generally accepted range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 58 publications
0
70
0
2
Order By: Relevance
“…17 The costs of different available treatments, including oral treatment with vasoactive drugs, intensive treatment by intravenous infusion, percutaneous transluminal angioplasty, by-pass surgery and exercise therapy have also been evaluated. 20, 21 Two exercise supervised programs, lasting 6 and 12 months each, showed favorable cost-effectiveness compared to endovascular revascularization or by-pass surgery. 1 Despite its cost-effectiveness, non-invasiveness and the minimal cardiovascular risk, the use of exercise as a treatment option is widespread for PAD.…”
Section: Discussionmentioning
confidence: 99%
“…17 The costs of different available treatments, including oral treatment with vasoactive drugs, intensive treatment by intravenous infusion, percutaneous transluminal angioplasty, by-pass surgery and exercise therapy have also been evaluated. 20, 21 Two exercise supervised programs, lasting 6 and 12 months each, showed favorable cost-effectiveness compared to endovascular revascularization or by-pass surgery. 1 Despite its cost-effectiveness, non-invasiveness and the minimal cardiovascular risk, the use of exercise as a treatment option is widespread for PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of procedural mortality and systemic complications are taken from Hunink et al, 77 as previously described. In addition, de Vries et al 78 also include rates for angiographic investigations. For an amputation, mortality rates are presented separately for patients below and above the age of 75 years; rates for systemic complications were assumed not to vary with age.…”
Section: Assessment Of Cost-effectivenessmentioning
confidence: 99%
“…The only other second-line treatment considered was PTA. This identified a further five economic evaluations (Hunink et al, 77 de Vries et al, 78 Holler et al, 79 Muradin and Myriam Hunink, 80 Visser et al…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…49 Cost-effectiveness and quality-of-life outcomes favor the performance of percutaneous therapy whenever feasible as a more effective treatment than exercise alone. 50 A matched-cohort study of 526 patients with intermittent claudication found significant advantages for a revascularization strategy (surgery or PTA) compared with medical therapy. 51 Revascularization was more effective than medical therapy for improvement in physical function, bodily pain, and walking distance.…”
Section: Sfa and Popliteal Artery Diseasementioning
confidence: 99%